Assessing the effects of service quality, student satisfaction, and student engagement on student loyalty a private higher education perspective - Konalingam, K.; Mahadevan, K.; Sivarajah, R. (University of Jaffna, 2021)
The main purpose of this study is to propose and empirically investigate a mediated mechanism of student satisfaction and student engagement to enhance student loyalty via educational service quality platforms. Hence, having a clear understanding of the relationship among higher education service quality, student satisfaction, student engagement, and student loyalty helps higher education institutions develop their marketing initiatives effectively. Four hundred (400) students were entitled to participate in the survey, and 346 respondents were used for further analysis. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyse the collected data, assess the model, and test hypotheses. Further, the findings of this study have confirmed that there is a positive and significant impact of the higher education service quality on student loyalty. Meanwhile, indirect effects of higher education service quality enhanced student loyalty via student satisfaction and engagement. To this end, the findings of the study provide unique cues for managers and private higher education practitioners in developing marketing strategies to enhance student loyalty.
Keywords: Private higher education; Service quality; Student satisfaction; Student engagement; Student loyalty